Analysis of Media Framing in Controversy Report of the Ustadz Hanan Attaki Bai'at on NU.Online - Imaroh, Nurul; Hadi, Sofyan; Jauhari, Minan; Wazis, Kun; Al Fajri, Syachirul A’dhom (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
The Ustadz Hannan Attaki Bai'at controversy by Kiai Marzuki was chosen as the focus of research because it attracted public attention and gave rise to various points of view. Bai'at was carried out on the sidelines of predecessor's birthday. Ahmad Noer, KH. Mustamar and KH. Murtadho Amin at the Sabilurrosyad Malang Islamic Boarding School generally contained five points. These include the oath of allegiance to the Republic of Indonesia and Nahdlatul Ulama. This research aims to analyze the news about the Bai'at controversy of Ustadz Hannan Attaki, who Kiai Marzuki guided at NU.Online. Through a media framing analysis approach, this research seeks to understand how the media builds issue representation and problem-solving in the context of this controversial Bai'at. The research method used is qualitative with content analysis. The analysis results show that media framing in coverage of the Bai'at Ustadz Hannan Attaki controversy by Kiai Marzuki tends to influence public understanding. At the problem definition stage, news articles tend to adopt a particular viewpoint that shapes the public's perception of Bai'at. In the problemsolving stage, news articles also offer recommendations and implications, which may influence the public's view of the controversy. This research contributes to understanding the role of the media in shaping public perceptions of controversial religious issues. The implications of this research can be used as a reference for a better understanding of media framing in a religious context and the importance of framing analysis in capturing issue representation and problemsolving in coverage.